A mediator-free whole-cell electrochemical biosensing system for sensitive assessment of heavy metal toxicity in water - Yang, Yuan; Fang, Zhen; Yu, Yang-Yang; Wang, Yan-Zhai; Naraginti, Saraschandra; Yong, Yang-Chun (Water science and technology, 2019)
A bioelectrochemical sensing system (BES) based on electroactive bacteria (EAB) has been used as a new and promising tool for water toxicity assessment. However, most EAB can reduce heavy metals, which usually results in low toxicity response. Herein, a starvation pre-incubation strategy was developed which successfully avoided the metal reduction during the toxicity sensing period. By integrating this starvation pre-incubation procedure with the amperometric BES, a sensitive, robust and mediator-free biosensing method for heavy metal toxicity assessment was developed. Under the optimized conditions, the IC50 (half maximal inhibitory concentration) values for Cu2+, Ni2+, Cd2+, and Cr6+ obtained were 0.35, 3.49, 6.52, 2.48 mg L−1, respectively. The measurement with real water samples also suggested this method was reliable for practical application. This work demonstrates that it is feasible to use EAB for heavy metal toxicity assessment and provides a new tool for water toxicity warning.